2020
DOI: 10.1016/j.bja.2020.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Association between intraoperative intravenous lidocaine infusion and survival in patients undergoing pancreatectomy for pancreatic cancer: a retrospective study

Abstract: Background: Intravenous lidocaine has been shown to reduce opioid consumption and is associated with favourable outcomes after surgery. In this study, we explored whether intraoperative lidocaine reduces intraoperative opioid use and length of stay (LOS) and improves long-term survival after pancreatic cancer surgery. Methods: This retrospective study included 2239 patients who underwent pancreatectomy from January 2014 to December 2017. The patients were divided into non-lidocaine and lidocaine (bolus injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 20 publications
4
45
0
2
Order By: Relevance
“…An increasing number of evidences have demonstrated that lidocaine could affect the development of multiple tumors including ovarian and breast cancer ( Gao et al, 2018 ; Khan et al, 2019 ; Liu et al, 2021 ). For example, it was reported that intravenous infusion of lidocaine during operation was associated with improved overall survival of patients with pancreatic cancer ( Zhang et al, 2020 ). Gao and colleagues suggested that the administration of lidocaine could enhance the apoptosis of breast cancer cells caused by cisplatin, as well as alleviating their metastasis in vivo ( Gao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of evidences have demonstrated that lidocaine could affect the development of multiple tumors including ovarian and breast cancer ( Gao et al, 2018 ; Khan et al, 2019 ; Liu et al, 2021 ). For example, it was reported that intravenous infusion of lidocaine during operation was associated with improved overall survival of patients with pancreatic cancer ( Zhang et al, 2020 ). Gao and colleagues suggested that the administration of lidocaine could enhance the apoptosis of breast cancer cells caused by cisplatin, as well as alleviating their metastasis in vivo ( Gao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The amide type LAs bupivacaine and lidocaine are on the WHO's list of essential drugs 9,10 and may also have antitumor effects for several tumor entities. 11,12 Furthermore, a recent study by Tohme et al observed that neutrophil extracellular traps (NETs), which are chromatin DNA released by PMNs, were implicated in colorectal carcinoma liver metastasis after surgical stress. 13 Galos et al could observe reduced NETosis in women treated with intravenous lidocaine during breast cancer surgery which might result in lower recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein and a member of the tyrosine kinase superfamily receptor [20]. Many EGFR gene alterations have been identi ed in gliomas, including ampli cations, deletions and single nucleotide polymorphisms (SNPs) [21][22][23], so it has served as a clinical marker in gliomas [21,23]. More importantly, Lidocaine suppressed the viability, migration, and invasion of lung cancer cells while induced apoptotic death via up-regulation of miR-539, which blocked EGFR signaling by directly binding with EGFR [24].…”
Section: Discussionmentioning
confidence: 99%